2004
DOI: 10.1111/j.1365-2966.2004.08345.x
|View full text |Cite
|
Sign up to set email alerts
|

Archival light curves from the Bamberg Sky Patrol: CF Octantis, 1964-76

Abstract: We use the archive of the Bamberg Sky Patrol to obtain light curves of the active K subgiant CF Octantis (HD 196818) for the interval 1964-76. Digitized images of the field near CF Oct were obtained with a flat-bed scanner. Aperture photometry was performed of photo-positives of these images. Using a transformation to second order in plate magnitude, and first order in B − V , for nine field stars for each plate, the B magnitudes of CF Oct were obtained for just over 350 plates. The estimated precision of an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Kroll et al 2001), as has been demonstrated by the work of Phillips & Hartmann (1978), Hartmann et al (1979), Hartmann et al (1981), Bondar' (1995, Alekseev & Bondar' (1998), Fröhlich et al (2002), and Innis et al (2004. Even though the photometric accuracy of a photographic brightness measure is low, averaging over dozens of measures nevertheless gives an accurate long-term mean light curve.…”
Section: Introductionmentioning
confidence: 76%
“…Kroll et al 2001), as has been demonstrated by the work of Phillips & Hartmann (1978), Hartmann et al (1979), Hartmann et al (1981), Bondar' (1995, Alekseev & Bondar' (1998), Fröhlich et al (2002), and Innis et al (2004. Even though the photometric accuracy of a photographic brightness measure is low, averaging over dozens of measures nevertheless gives an accurate long-term mean light curve.…”
Section: Introductionmentioning
confidence: 76%
“…In the GCVS (Samus et al 2010), the star is described as an RS CVn‐type variable with maximal brightness V = 8.27 mag and relatively large photometric variations ∼0.3 mag. Early archival observations from the BOSSS were recently digitized and analysed by Innis et al (2004).…”
Section: Cf Oct An Active Spotted Giant Starmentioning
confidence: 99%
“…CF Oct was observed on 352 plates in the period 1964–1976. Innis et al (2004) performed aperture photometry and phase dispersion minimization (PDM) light‐curve analysis. In Innis et al (2004) we discussed the methods for photographic plate digitization, the plate photometry and the transformation from B to V magnitude of the star.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations